2014
DOI: 10.1073/pnas.1414665111
|View full text |Cite
|
Sign up to set email alerts
|

Bnip3 mediates doxorubicin-induced cardiac myocyte necrosis and mortality through changes in mitochondrial signaling

Abstract: Significance We provide new, exciting evidence for a previously unidentified signaling pathway that mechanistically links mitochondrial respiratory chain defects to necrosis and heart failure induced by the chemotherapy agent doxorubicin (DOX). We specifically show that DOX disrupts protein complexes between the key respiratory chain proteins, including uncoupling protein 3 and cytochrome c oxidase, resulting in abnormal mitochondrial respiration and necrosis thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 42 publications
8
136
2
2
Order By: Relevance
“…CYP27B1 , which was 13.23-fold up-regulated in CEM/ADR5000 cells, is important for drug metabolism74. BNIP3 plays role in oxidative stress75 and was 10.41-fold up-regulated in our resistant cell line. TCF7 is an anti-apoptotic gene76 and was 17.66-fold down-regulated.…”
Section: Discussionmentioning
confidence: 81%
“…CYP27B1 , which was 13.23-fold up-regulated in CEM/ADR5000 cells, is important for drug metabolism74. BNIP3 plays role in oxidative stress75 and was 10.41-fold up-regulated in our resistant cell line. TCF7 is an anti-apoptotic gene76 and was 17.66-fold down-regulated.…”
Section: Discussionmentioning
confidence: 81%
“…BNIP3 is an important regulator of cardiomyocyte mitochondrial function and survival during ischemic/hypoxia injury [10, 47]. That is, the mitochondrial perturbations triggered by BNIP3 gene activation were found to parallel opening of the mitochondrial permeability transition pore, mitochondrial membrane potential loss, and cell death [48]. Although HIF-1α is an upstream molecular target of BNIP3, [22] we showed that HIF-1α did not completely parallel the alterations in BNIP3, suggesting that there may be other unrecognized upstream molecular pathways involved in BNIP3 regulation in RV failure.…”
Section: Discussionmentioning
confidence: 99%
“…107 Bnip3 also stimulates myocardial necrosis in response to doxorubicin treatment by disrupting formation of mitochondrial protein complexes between the key respiratory proteins. 108 Thus, what determines the role of Bnip3 in promoting cell death or survival through mitochondrial autophagy remains to be elucidated in the heart.…”
Section: Nix/bnip3l and Bnip3mentioning
confidence: 99%